The Influence of Shopee Free Shipping Vouchers on User Purchase Decisions: A Case Study of Rengas Pulau Subdistrict - Muhammad Wahyudi; Muhammad Syahputra Novelan (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
The rapid development of e-commerce has made promotional strategies increasingly vital, with free shipping vouchers standing out as one of the most effective tools to enhance consumer engagement. Shopee, as a leading player in the digital marketplace, has effectively utilized this strategy to boost user transactions by consistently offering free shipping vouchers. This study aims to analyze the influence of such vouchers on consumer purchasing decisions, focusing on users in Kelurahan Rengas Pulau. A quantitative research approach was adopted using a descriptive associative method. Data collection was carried out through the distribution of questionnaires to 200 respondents, selected using purposive sampling techniques. The data were then analyzed using regression analysis to determine the relationship between the use of free shipping vouchers and consumer purchasing behavior. The results of the regression analysis showed a strong and statistically significant relationship, with a regression coefficient of 0.620 and a p-value of 0.000. This suggests that the presence of free shipping vouchers substantially increases the likelihood of consumers making purchases. These findings confirm that free shipping promotions are a key factor in shaping consumer behavior, especially in suburban areas like Kelurahan Rengas Pulau. In conclusion, free shipping vouchers not only attract potential customers but also contribute to an increase in sales transactions. Businesses and e-commerce platforms should consider incorporating similar promotional tactics to maintain competitiveness and enhance customer satisfaction. This study affirms the positive and significant effect of Shopee’s free shipping incentives on user purchasing decisions, highlighting their strategic importance in today’s competitive digital marketplace